Merchanting and Current Account Balances. (21st October 2015) - Beusch, Elisabeth; Döbeli, Barbara; Fischer, Andreas M.; Yeşin, Pinar
Abstract: Merchanting is goods trade that does not cross the border of the firm's country of residence. Merchanting grew strongly in the last decade in several European economies and has become an important determinant of these countries' current account. Because merchanting firms reinvest their earnings abroad to expand their international activities, this practice raises national savings in the home country without increasing domestic investment. This paper examines the empirical linkages between merchanting and the current account balance. Using a sample of 53 countries during 1980–2011, it shows that merchanting activity is a determinant of the medium‐term current account balance.